Two-Dimensional Digital Beam Steering Based on Liquid Crystal Phase Gratings - Mario García de Blas; Morten Andreas Geday; Jose Manuel Otón; Xabier Quintana Arregui (Applied Sciences, 2021)
Electrically tunable phase gratings are able to steer an incoming light beam without employing movable parts. Here, we present the design and implementation of a 2D beam steering device by cascading two orthogonal 1D liquid crystal (LC) based phase gratings, each having an array of 72 rectangular individually controlled pixels and driven by a custom 12-bit Pulse-Width Modulation (PWM) electrical driver. High-resolution structures in glass wafers coated with transparent Indium-Tin Oxide (ITO) have been prepared using Direct Laser Writing (DLW) techniques. With DLW, a high number of pixels can easily be drawn with an interpixel space of less than 3 μm, leading to devices with a high fill factor. The active area of the cascaded device is 1.1 × 1.1 mm2. We present a 72 × 72 point efficiency map corresponding to a maximum diagonal steering angle of 1.65°. Special attention has been paid to make the device compatible with space application by avoiding electronics in the active area.